Saudi Arabia: strategic environment and nuclear security (Revista da EGN, 2023)
This article aims to discuss the possibility for the Kingdom of Saudi Arabia to develop nuclear weapons to balance Iran, should the Persian state become a nuclear power in the Middle East region. Thus, the research was developed based on the statement by Crown Prince Mohammed bin Salman who said his country woulddevelop a nuclear bomb if Tehran took the first step in this direction. In addition, it was sought to work with an approach as close as possible to the internal vision of the Saudi Arabian government, with statements from Saudi political personalities and government officials. This work addresses the Saudi regional context; the Iranian threat; Saudi Arabia’s deterrent alternatives; and, finally, the Kingdom’s capabilities in developing its own nuclear program.